(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In this paper theoretical approach with proven mathematical model is described for a speed-sensor less startup method particularly for induction motor driven by a modular multilevel cascade inverter based on double-star chopper cells (MMCI-DSCC) from standstill to middle speed using PI controller. These types of motor are more suitable for large capacity fan – or blower type of load. While implementing this technique closed loop method is used as it is more robust and reliable as compared to open loop system. The simulation of above system is done in this paper and results are considerably good. INDEX TERMS: Induction Motor Drives, Closed loop system, Modular multilevel converter (MMC), PI controller.